CagA-positive and CagA-negative Helicobacter pylori strains differentially affect the expression of micro RNAs 21, 92a, 155 and 663 in human umbilical vein endothelial cells - Kalani, M.; Hodjati, H.; GhamarTalepoor, A.; Samsami Dehaghani, A.; Doroudchi, M. (Cellular and Molecular Biology, 2017)
Given that the basic mechanism of the effect of Helicobacter (H.) pylori in the induction of atherosclerosis remains unknown and regarding the regulatory role of micro RNAs (miRNAs) in endothelial cell (EC) functions, we aimed to investigate the effect of H. pylori on the expression of miRNAs involved in atherosclerosis (atheromiRs) and their correlation with apoptosis in human umbilical vein EC (HUVEC). HUVECs were treated with different cytotoxin associated gene A (CagA) positive and negative H. pylori derived products, then the levels of apoptosis and miR-21, 92a, 155 and 663 were measured using flowcytometry and real time-PCR methods, respectively. Although, comparing induced apoptosis and necrosis in HUVECs revealed that water extract of CagA+ H. pylori (HpWE) was more potent than CagA- one and H. pylori lipopolysacharide (Hp-LPS), no significant difference was observed between LPS extracted from CagA+ and CagA- strains. Besides, CagA+ HpWE significantly increased the levels of anti-apoptotic miR-21, and inflammatory miRNAs 155 and 663 but not miR-92a. A positive correlation was observed between apoptosis and necrosis and miR-155 as well as the expressions of miR-21 with miR-155 (P=0.024) and miR-663 (P=0.0001). As H. pylori products differentially influenced phenotypic and epigenetic changes in ECs pictured in apoptosis and in the expression of atheromiRs, we suggest that the presence of CagA molecule accompanied by these atheromiRs may act as beneficial biomarkers predicting ECs apoptosis as a sign of plaque rupture.